Effects of team-based learning on problem-solving, knowledge and clinical performance of Korean nursing students. - Kim, Hae-Ran; Song, Yeoungsuk; Lindquist, Ruth; Kang, Hee-Young (Nurse Education Today, 2016)
Summary Background Team-based learning (TBL) has been used as a learner-centered teaching strategy in efforts to improve students' problem-solving, knowledge and practice performance. Although TBL has been used in nursing education in Korea for a decade, few studies have studied its effects on Korean nursing students' learning outcomes. Objectives To examine the effects of TBL on problem-solving ability and learning outcomes (knowledge and clinical performance) of Korean nursing students. Design Randomized controlled trial. Participants 63 third-year undergraduate nursing students attending a single university were randomly assigned to the TBL group ( n = 32), or a control group ( n = 31). Methods The TBL and control groups attended 2 h of class weekly for 3 weeks. Three scenarios with pulmonary disease content were employed in both groups. However, the control group received lectures and traditional case study teaching/learning strategies instead of TBL. A questionnaire of problem-solving ability was administered at baseline, prior to students' exposure to the teaching strategies. Students' problem-solving ability, knowledge of pulmonary nursing care, and clinical performance were assessed following completion of the three-week pulmonary unit. Results After the three-week educational interventions, the scores on problem-solving ability in the TBL group were significantly improved relative to that of the control group ( t = 10.89, p < .001). In addition, there were significant differences in knowledge, and in clinical performance with standardized patients between the two groups ( t = 2.48, p = .016, t = 12.22, p < .001). Conclusion This study demonstrated that TBL is an effective teaching strategy to enhance problem-solving ability, knowledge and clinical performance. More research on other specific learning outcomes of TBL for nursing students is recommended.